Multidetector-row Computed Tomographic Angiography in the Planning of the Local Perforator Flaps - Badiul, Pavlo O. (Plast Reconstr Surg Glob Open, 2015)
The perforator vessels are highly variable in number, localization types, hemodynamic specifications, and the anatomical interactions with other structures. For these reasons, the identification of the best perforator before the operation is very important for the choice of the main feed vessel and the design of the perforator flap. METHODS: The authors retrospectively analyzed all cases in which multiple detector computed tomography (MDCT) with 3-dimensional (3D) image reconstruction was used in the preoperative planning in preparation for the reconstruction with local perforator flaps, which took place between July 2012 and December 2014 in the hospital. RESULTS: A total of 24 people were examined and underwent operations with 26 reconstructions using local perforator flaps. All perforators, which were identified during the MDCT with 3D reconstruction examination, were located intraoperationally without any errors. CONCLUSIONS: The preoperative MDCT with 3D reconstruction investigations of the topographic anatomical specifics of the perforator vessel on which the formation of the flap feed pedicle is planned allow for the fast and precise identification of the perforation at the preoperative stage while minimizing the amount of injury caused to the perforator during the operation and decrease the operation time.